SEISMIC FIELD OPERATIONS AND ANALYSIS OF 1966 LAKE SUPERIOR EXPERIMENT - DE LA Barre, Kenneth (1966)
Four Canadian universities participated in the experiment and recorded the explosions at the following approximate locations: (1) Yorktown, Saskatchewan, through Edmonton to Whitecourt in western Alberta (1100 to 2000 kilometer range) also along a 400 kilometer arc from Cold Lake to Bow Island, Alberta. Linked up with University of Manitoba profile. (2) Southeastern Manitoba and southwestern Ontario. (3) Southwest of Lake Nipigon to Lake Nyanilini, northwest of Fort Churchill and east of Lake Superior. These reports included, but were not restricted to, the following data: (a) Co-ordinates of recording units for each shot. (b) First arrival times. (c) Amplitudes of first arrivals. (d) Reproductions of first arrivals. (e) Description of recording instruments and calibration information.